Effect of Charge Transfer Resistance on Morphology of Lithium Electrodeposited in Ionic Liquid. Issue 12 (1st January 2016) - Sano, Hikaru; Kitta, Mitsunori; Matsumoto, Hajime
Abstract : Secondary batteries based on lithium (Li) metal anodes are a potential candidate for next-generation energy storage devices, but their practical commercialization has so far been greatly limited by safety issues and cycle-life limitations associated with the formation of Li dendrites. This study therefore looks at the morphology of Li that is electrodeposited in room-temperature ionic liquids (RTILs) with a view to determining the most suitable electrolyte properties. Particular focus is given to how the distribution of nucleation points changes in relation to the charge transfer resistance of the RTIL, which is varied by changing the viscosity of the electrolyte. Through this, it is found that a more viscous electrolyte with a higher charge transfer resistance produces Li deposits that are more evenly distributed and smaller in size.